Outcomes of percutaneous endoscopic gastrostomy (PEG) in HIV patients - Nikhitha Mantri; Haozhe Sun; Sameer Datta Kandhi; Nishant Allena; Muhammad Yasir Anwar; Vibha Hayagreev; Shalini Penikilapate; Ahmed Alemam; Hassan A Muntazir; Trishna Acherjee; Harish Patel; Jasbir Makker (BMC Gastroenterology)
Abstract Background Percutaneous Endoscopic Gastrostomy (PEG) tube insertion, a routine procedure for long-term enteral nutrition, serves as a crucial intervention for patients who are incapable of tolerating oral intake or meeting adequate nutritional requirements. PEG tube placement carries complications like bleeding and infection. Impact of PEG tubes on the 30-day and long-term mortality in HIV patients is unknown. Despite the ongoing utilization of PEG tubes in HIV patients, a comprehensive exploration of its outcomes is yet to be explored. We intended to study the impact of HIV positive status on post-PEG mortality and review other PEG tube related complications. Methods Our study comprised a total of 639 PEG tubes placed on 461 unique patients, from which 85 patients (n = 18%) were HIV positive. We reviewed all these PEG tube patients at our institution and compared their complications and mortality outcome between the two groups of HIV positive as against HIV negative. Results Our findings reveal a statistically significant increase (p-value 0.001) in post-PEG insertion site bleeding in the HIV group (15.3%) compared to the non-HIV group (4.5%). This difference occurred despite no notable variations in laboratory parameters such as platelet count and (international normalized ratio), as well as similar usage of anticoagulant or antiplatelet medications between the two groups. Notably, the 1-year mortality rate in the HIV group stands at 37.6% (p < 0.001), contrasting sharply with the non-HIV group’s rate of 17.8%. Conclusion This study underscores the need for heightened vigilance and tailored management strategies when considering PEG tube procedures in the context of HIV, given the observed elevated bleeding risks and increased 1-year mortality rates in this patient population. Further research is warranted to elucidate the underlying factors contributing to these outcomes, facilitating the development of targeted interventions to optimize the care of HIV patients undergoing PEG placement.